PROMISING AREAS OF USING HISTORICAL AND PEDAGOGICAL EXPERIENCE TO IMPROVE THE LINGUISTIC PROFESSIONAL TRAINING - Mukan, Nataliya; Havryliuk, Marianna; Levko, Mariana; Kobryn, Nadiia; Zapotichna, Mariia (Revista Conhecimento Online: Diversidade e Inclusão Social, 2021)
In a modern globalized world, knowledge of a foreign language is important, determines the relevance of high-quality training of specialists in foreign language communication. Foreign language proficiency is a significant condition for establishing and maintaining international business contacts, intensifying professional interaction with foreign colleagues. The Bologna Convention also proclaims knowledge of foreign languages as a necessary basis for the mobility of students, teachers and scientists for access to education, research, teaching and training in the European Region. All these factors justify the economic value of knowledge of foreign languages and become an indispensable component of the professional training of future specialists. Competitiveness of specialists depends on the ability to read and translate professional foreign literature, on the formation of skills to listen to lecture material and reports in a foreign language during conferences, round tables and seminars; from the ability to participate in an idiosyncratic conversation on professional and business topics; from the ability to find the necessary information on the Internet or in any other foreign sources; from the ability to prepare and conduct a presentation on a selected topic.